ENRICHMENT OF MUD CRAB PARENTS (Scylla serrata) FEED WITH THE ADDITION OF RED FRUIT OIL (Pandanus conoideus) ON THE DEVELOPMENT OF OVARY MATURITY TIME AND NUMBER OF LARVAE - Hidayah, Elmi; Nurhaidin, Nurhaidin; Satriyanto, Budi (Jurnal Segara, 2024)
This study aims to determine the effect of the addition of Papuan red fruit oil supplements (Pandanus conoideus) as a result of red fruit extraction, on the development of ovaries and the length of maturation time of mangrove crab ovaries (Scylla serrata). Red fruit (Pandanus conoideus) is an endemic Papuan plant that is believed to cure several diseases and can be used as a supplement because it contains active compounds including fatty acids in the form of triglycerides and antioxidant compounds such as beta-carotene and tocopherols. Experiment with feeding fresh feed to Mangrove Crab broodstock, weighing 400-500 g/head. The experiment was conducted using a Complete Random Design with three feed compositions and three individuals as replicates. Feed A (control): Decapterus sp.100 g; Feed B : Decapterus sp. 23 g, 40 g Shelled Squid, and 37 g Red Fruit Oil; Feed C: Decapterus sp fish 41 g, squid shell 24 g, and Red Fruit Oil 35 g. The parent maintenance container uses a transparent plastic container with water circulation (waterflow). The parameters measured were the length of time to reach ovarian maturity and the number of larvae produced by mangrove crabs (Scylla serrata). The data was analyzed with INOVA. The results of the study showed that the mother crab fed Red Fruit Oil supplement had a longer time to mature ovary faster than the mother crab fed without Red Fruit Oil.